45.5k views
0 votes
If a:b = (1/a + 1/c):(1/b + 1/c), and if a ≠ b, express c on terms of a and b

User TruthSeekr
by
4.8k points

1 Answer

6 votes

Given:

a:b = (1/a + 1/c):(1/b + 1/c),a ≠ b,

Required:

Express c on terms of a and b​.

Step-by-step explanation:

The given expression is:


(a)/(b)=((1)/(a)+(1)/(c))/((1)/(b)+(1)/(c))

Solve it by cross multiplication as:


\begin{gathered} a((1)/(b)+(1)/(c))=b((1)/(a)+(1)/(c)) \\ (a)/(b)+(a)/(c)=(b)/(a)+(b)/(c) \\ (a)/(b)-(b)/(a)=(b)/(c)-(a)/(c) \end{gathered}

Solve by taking L.C.M.


\begin{gathered} (a^2-b^2)/(ab)=(b-a)/(c) \\ ((a-b)(a+b))/(ab)=(b-a)/(c) \\ ((a-b)(a+b))/(ab)=-((a-b))/(c) \\ (a+b)/(ab)=-(1)/(c) \\ c=-(ab)/(a+b) \end{gathered}

Final Answer:

Thus c in terms of a and b is:


c=-(ab)/(a+b)

User Lala
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.